Anti Angiogenic Activity of Vitex Agnus Castus Methanol Extract In Vivo Study: Anti angiogenic Activity of Vitex agnus castus Methanol Extract - Hayder B Sahib,; Adeeb A Al-Zubaidy,; Ghaith A Jasim, (Iranian Journal of Pharmaceutical Sciences, 2016)
This study aimed to investigate the anti-angiogenic activity of Vitex agnus castus methanol extract in vivo. Eggs were incubated for three days, small whole made on the fine pinpoint. The next day, the egg’s sac was penetrated and a small frame was made in the shell. The window was resealed and the eggs were returned to the incubator until day 10 of chick embryo development, 20 μl of 500mg/ml of the methanol extract was transferred to the Chick Embryo Chorioallantoic Membrane (CAM), and eggs incubated for 72 hours (n = 6); The zone of inhibition was calculated as mean of inhibition area in millimetre (mm) ±standard deviation (SD). Functional groups of the chemicals component inside the extract has been identified by Fourier transform infrared spectroscopy FT-IR and High performance liquid chromatography HPLC was used to identify the most likely causative agent. The results showed that the zones of inhibition area more than 10 mm. FT-IR showed that some of the identified functional group may relate to flavonoids. Casticin has been identified in methanol extract. Because of the above results the mechanism of anti-angiogenic activity for the methanol extract of the Vitex agnus castus may be related to the Casticin which has the ability to block the VEGF-receptor, thereby inhibiting the angiogenesis process.